Oil Price Shocks and Currency Denomination - Hans-Werner Wohltmann; Roland C. Winkler (Kiel University, Department of Economics, 2005)
The paper analyzes the dynamic effects of anticipated price increases of imported raw materials upon two large open economies. It is assumed that the economies have an asymmetric macroeconomic structure on the supply side and are dependent upon a small third country for oil or raw materials imports. The dynamic behavior of several macroeconomic variables is discussed both under US dollar and Euro-currency denomination. It is shown that with Euro-currency denominated oil the stagnationary effects of oil price increases upon both the domestic and foreign economy are reduced. The paper also discusses several monetary policy responses to oil price shocks.
Keywords: F42; E63; Q43; 330; oil price shocks; international policy coordination; currency denomination; Mineralölpreisschock; Zwei-Länder-Modell; Konjunkturzusammenhang; Zeitkonsistenz; Internationale wirtschaftspolitische Koordination; Währungsumrechnung; Makroökonomischer Einfluss; Theorie